Desempenho agronômico de cultivares de soja em duas épocas de semeadura no Arenito Caiuá - Barbosa, Mauro Cezar (2009)
Soybean establishes, currently, one of the most important products in the Brazilian economy, and it is, therefore, the focus of research. In order to evaluate the agronomic performance of the soybean cultivars plants in Umuarama (northwest of Paraná), were conducted tests of competition of soybean cultivars, with design in randomized blocks, with four replicates, in three agricultural years (2005/2006, 2006/2007 and 2007 2008) and two sowing dates (27/10 and 10/11). The evaluated cultivars were BRS 255 RR, CD 202, CD 214 RR (early maturation), BRS 232, BRS 246 RR, CD 208 (semiearly maturation), BRS 262 and CD 218 (medium maturation). The evaluated agronomic characteristics were: number of days to maturity, plant height, height of insertion of the first pods, number of pods per plant, grain yield and weight of 100 seeds. The data were submitted to analysis of variance over and the ramifications of the interactions were also done. Based on the results, it was found: in the first agricultural year, the mass and grains productivity increasing were favored by a climate regularity between the stages R4 - R5; in the second agricultural year it was possible to identify the superiority comparing to the first sowing date as for the components production (weight of 100 seeds, number of pods per plant and grain yield) as well as to identify distinct superiority of some cultivars such as BRS 262 (referring to the number of pods), BRS 232 (about the mass of 100 seeds) and BRS 246 RR (in terms of productivity).